New Art Therapy Technology – Quilling - Iskakova, Zhansaya; Kassymova, Roza; Zhamalova, Tansholpan; Chalimbayeva, Anel; Utegenova, Kamilya (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
This research work aims to study the main features of quilling technology in art therapy, as well as its impact on group and individual consciousness. The study’s methodological approach was the search and theoretical analysis of thematic literature studying the quilling technique of art therapy, as well as art therapy in general. In this article, the theoretical method, the method of comparative analysis, as well as the method of pedagogical experiment were used. As a result of the scientific research, the technology of art therapy as such was analysed, and its components and influence on children and adults were studied. Also, after performing a pedagogical experiment, the influence of quilling technology on students of Al-Farabi Kazakh National University was studied, and the results were analysed. According to the results of the pedagogical experiment, quilling art has a positive effect on individuals, as well as on the general mood of the group, and the use of the quilling technique as an art-therapeutic tool brings positive changes to the psychosomatics of an individual and a group in general. This research work is of practical importance in the study of the art of quilling as an art-therapeutic method in the development of fine motor skills in the hands of adults and children, as well as the improvement of the psychological state after psychological traumas of various kinds.